A porous cobalt-based MOF with high CO2 selectivity and uptake capacity. Issue 37 (25th March 2015) - Du, Liting; Lu, Zhiyong; Ma, Mengtao; Su, Fan; Xu, Li
Abstract : A porous cobalt-based metal–organic framework [CoL 2− ] n has been designed by self-assembling [Co2 (COO)4 ] paddlewheel SBUs and a novel trigonal hetero–functional ligand. [CoL 2− ] n exhibits large CO2 uptake and selectivity. Abstract : A porous cobalt-based metal–organic framework [CoL 2− ] n (L = 5-(pyrimidin-5-yl) isophthalic acid) (termed NJFU-2), has been designed by self-assembling [Co2 (COO)4 ] paddlewheel SBUs and a novel trigonal hetero-functional ligand. Moreover, the activated sample NJFU-2a exhibits a moderate BET surface area of 1223 m 2 g −1, large CO2 uptake (6.14 wt% at 0.15 bar and 298 K) and high selectivity for CO2 over CH4 and N2 at room temperature, estimated by the Ideal Adsorbed Solution Theory (IAST).